PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BALAI WILAYAH SUNGAI SULAWESI III - Turunan, Rita Anugrahni (Katalogis, 2017)
The purpose of this research out the influence of the leadership style which are delegative leadership style, autocratic leadership style, participative leadership style both simultaneously and partially to the casual employee performance on Balai Wilayah Sungai Sulawesi III. The population in the research is a casual employee on Balai Wilayah Sungai Sulawesi III with samples obtained amounted to 88 people. Meanwhile, the analysis technicque is using multiple regression analysis. The research result shows that the leadership style which delegative leadership style, autocratic leadership style, participative leadership style have simultaneously significant influence to the casual employees performance on Balai Wilayah Sungai Sulawesi III. This result is supported by the simultaneous corelation coefficient of 42,9%Â shows that either correlation or relations between those variables to the casual employees on Balai Wilayah Sungai Sulawesi III have strong relation. The research result shows that the leadership style which are delegative leadership style, autocratic leadership style, participative leadership style each variables have partially significant influence to the casual employeesâ€™ performance on Balai Wilayah Sungai Sulawesi III.